Відповідь:
а) х(х-3)=0
Розв'яжемо шляхом розкладання на множники:
x = 0 x - 3 = 0
x₁ = 0 x₂ = 3
б) у(5-у)=0
у = 0 5 - у = 0
у₁ = 0 у₂ = 5
в) 3z * (z+4) = 0
z(z*4) = 0
z = 0 z+4 = 0
z₁ = 0 z₂ = -4
г) 2х * (5 - 2х) = 0
х(5-2х) = 0
х = 0 5-2х = 0
х₁ = 0 х₂ = 2,5
ґ) x²-12x=0
х(х-12) = 0
х = 0 х-12 = 0
х₁ = 0 х₂ = 12
д) 4x²+x=0
х(4х + 1) = 0
х = 0 4х + 1 = 0
х₁ = 0 х₂ = -0,25
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
а) х(х-3)=0
Розв'яжемо шляхом розкладання на множники:
x = 0 x - 3 = 0
x₁ = 0 x₂ = 3
б) у(5-у)=0
Розв'яжемо шляхом розкладання на множники:
у = 0 5 - у = 0
у₁ = 0 у₂ = 5
в) 3z * (z+4) = 0
z(z*4) = 0
z = 0 z+4 = 0
z₁ = 0 z₂ = -4
г) 2х * (5 - 2х) = 0
Розв'яжемо шляхом розкладання на множники:
х(5-2х) = 0
х = 0 5-2х = 0
х₁ = 0 х₂ = 2,5
ґ) x²-12x=0
Розв'яжемо шляхом розкладання на множники:
х(х-12) = 0
х = 0 х-12 = 0
х₁ = 0 х₂ = 12
д) 4x²+x=0
Розв'яжемо шляхом розкладання на множники:
х(4х + 1) = 0
х = 0 4х + 1 = 0
х₁ = 0 х₂ = -0,25